Uma leitura kantiana da lógica deôntica standard - Secco, Gisele Dalva (2006)
The current dissertation is the result of an investigation about the semantic of deontic logic. Restricting to the propositional version, the work had as the main objective of study some lectures of the philosopher J. Hintikka which semantic proposal for deontic logic includes a re-interpretation of an important notion in Kant s philosophy: the notion of a Kingdom of Ends. Kant also figures in the Hintikka proposal through the illustration of one of the results of his matter, it means, the distinction between logical and deontic consequence, from which the so called Kant s Principle is an example. Having as the objective the exposition of this proposal, it has chosen to situate it in a discussion about the convenience of formalizations has a tool of philosophical analysis. Therefore, the proposal of Hintikka figures as an example of formalization which the results can have relevant philosophical features. The general exposition of the Kantian formulations of the Categorical Imperative, especially the formulation of the Kingdom of Ends (the subject matter of the first chapter), it has as an aim to point the most relevant features in Kantian practical philosophy for doing the analysis that accomplishes on the third chapter.